Artificially Sweetened Beverages and Stroke, Coronary Heart Disease, and All-Cause Mortality in the Women's Health Initiative. Issue 3 (March 2019) - Mossavar-Rahmani, Yasmin; Kamensky, Victor; Manson, JoAnn E.; Silver, Brian; Rapp, Stephen R.; Haring, Bernhard; Beresford, Shirley A.A.; Snetselaar, Linda; Wassertheil-Smoller, Sylvia
Abstract : Background and Purpose—: We examine the association between self-reported consumption of artificially sweetened beverages (ASB) and stroke and its subtypes, coronary heart disease, and all-cause mortality in a cohort of postmenopausal US women. Methods—: The analytic cohort included 81 714 women from the Women's Health Initiative Observational Study, a multicenter longitudinal study of the health of 93 676 postmenopausal women of ages 50 to 79 years at baseline who enrolled in 1993 to 1998. This prospective study had a mean follow-up time of 11.9 years (SD of 5.3 years.) Participants who completed a follow-up visit 3 years after baseline were included in the study. Results—: Most participants (64.1%) were infrequent consumers (never or <1/week) of ASB, with only 5.1% consuming ≥2 ASBs/day. In multivariate analyses, those consuming the highest level of ASB compared to never or rarely (<1/wk) had significantly greater likelihood of all end points (except hemorrhagic stroke), after controlling for multiple covariates. Adjusted models indicated that hazard ratios and 95% confidence intervals were 1.23 (1.02–1.47) for all stroke; 1.31 (1.06–1.63) for ischemic stroke; 1.29 (1.11–1.51) for coronary heart disease; and 1.16 (1.07–1.26) for all-cause mortality. In women with no prior history of cardiovascular disease or diabetes mellitus, high consumption of ASB was associated with more than a 2-fold increased risk of small artery occlusion ischemic stroke hazard ratio =2.44 (95% confidence interval, 1.47–4.04.) High consumption of ASBs was associated with significantly increased risk of ischemic stroke in women with body mass index ≥30; hazard ratio =2.03 (95% confidence interval, 1.38–2.98). Conclusions—: Higher intake of ASB was associated with increased risk of stroke, particularly small artery occlusion subtype, coronary heart disease, and all-cause mortality. Although requiring replication, these new findings add to the potentially harmful association of consuming high quantities of ASB with these health outcomes. Abstract : Supplemental Digital Content is available in the text.